Interview with Les Vanoncini, director of Alumni and Community Affairs, September 23, 1967 (1967)
[00:00:03] Interviewer introduces Les Vanoncini, director of Alumni and Community Affairs at Cal Poly [00:00:28] Vanoncini discusses the number of alumni, and how many participate in the association [00:01:10] Interviewer asks what the Alumni Association does, seeking assistance to get the best students to attend the campus [00:02:20] Vanoncini talks about the schedule for the alumni planned activities during Homecoming: bonfire, concert, parade, etc [00:04:11] Interviewer asks about future plan for the Alumni Association [00:04:58] Interviewer begins to wrap up interview